Work Motivation in Project Management: Are We Still Interested? A Bibliometric Analysis of Doctoral Dissertations (European Journal of Behavioral Sciences, 2018)
This study included a review and bibliometric analysis of doctoral dissertations on work motivation in project management. Designed to be an exploratory review, work motivation in project-based organizations, and in permanent organizations that undertake projects were considered. 840 doctoral theses from the period 1972-2018 were analyzed. The results showed an increasing number of these being published on the topic of work motivation, and increasingly on allied topics of leadership, job satisfaction, and project management context. Further, a substantial number of these studies are grounded in phenomenology and grounded theory-adopting interviews as a choice of methodology. Empirical studies were also found to be popular, especially in the early decades. Implications for further studies on the topic of work motivation is presented.